Utilization of Pictorial Analogy and Colored Sticks in Teaching Chemical Equation - Cabubas, Donna N; Mustacisa-Lacaba, Marife (Jurnal Penelitian dan Pembelajaran IPA, 2023)
Chemical Equations are valuable tool for helping students comprehend chemical reactions, as these reactions are intricately connected to human activities. The analysis of blood and tissue samples, the dating of fossils, the investigation of antiquity, and the detection and characterization of planets are a few of these chemical reactions. In order to understand more about how well students understood chemical equations using the coloured stick model and pictorial analogies, this study employed a quasi-experimental methodology. This research design, sought to establish a cause-and-effect relationship because groups were not randomly assigned. Two sections of Grade 10 students participated in this study as respondents, and they were selected depending on their availability and willingness to participate in the study. It was discovered that the difference in scores gained by the two groups is statistically significant. The computed absolute value of t (-4.09) is higher than the t-critical (2.08) with a p-value of 0.00, lower than the level of significance of 0.05, which proved that the pictorial analogy group performs better than the coloured stick group. It is recommended that, whenever applicable, the model be repeated in a variety of chemistry topics and courses that frequently use numerical presentation.